Le sens de la fiction ludique : jeu, récit et effet de monde - Antoine Dauphragne (Strenae)
In the contemporary gaming landscape marked by transmedia packages, fiction occupies a place both central and diffused. It can be seen in the narrative material that completes the game’s product line, in the imaginary universes that accompany it, or in the very principle of certain types of games. Fiction shares a certain number of characteristics with games, which partly explains the frequency with which they are brought together. At the same time, cultural dynamics and media developments that began to emerge in the 1970s are important explanatory factors. Today, from Star Wars to Pokémon, and from Lord of the Rings to World of Warcraft, the omnipresence of game fiction is matched only by its versatility as a promotional vehicle, driving the game and making imaginary worlds. The playful and fictional dimensions tend to merge into each other, in a movement redefining the boundaries of gaming.